How short video addiction affects risk decision-making behavior in college students based on fNIRS technology - Zhang, Shu; Li, Shiyi (Frontiers in Human Neuroscience, 2025)
IntroductionShort video addiction is an emerging form of Internet behavioral addiction characterized by dependent, inappropriate, or excessive use of short video applications. This phenomenon significantly affects decision-making processes and warrants further investigation. Despite the growing prevalence of short video addiction, research on its impact on risky decision-making abilities remains limited. To address this gap, the present study contributes to this critical issue by incorporating neurophysiological data.MethodsUsing functional Near-Infrared Spectroscopy (fNIRS) brain imaging technology and the Balloon Analogue Risk Task (BART) experimental paradigm, this study explored the decision-making behaviors and brain activity of individuals with short video addiction (Individuals with SVA) under varying short video background cues. Adopting a mixed experimental design, the study examined decision-making ability and brain activation as dependent variables across two groups (addiction and control), two outcomes (gain and loss), and two background cue conditions (with and without cues). A total of 45 participants were included in the study: 23 in the addiction group and 22 in the control group.ResultsBehavioral results revealed that individuals with short video addiction demonstrated higher risk-taking tendencies, shorter reaction times, and higher rates of balloon explosions, particularly when exposed to short video cues. Neural data indicated heightened sensitivity to short video cues among individuals with addiction compared to healthy controls. Specifically, the right orbitofrontal cortex (OFC) and right frontopolar area (FPA) exhibited increased activation during risk decision-making with short video cues in the addiction group, while the control group showed no activation in these regions. Additionally, Individuals with SVA displayed greater sensitivity to loss outcomes, with significant OFC activation observed in response to losses but not gains. In risk decision-making scenarios involving short video cues, notable activation was observed in the FPA and left dorsolateral prefrontal cortex (DLPFC) among Individuals with SVA when encountering reward loss. However, no significant differences were observed between the two groups in risk decision-making under the background without short video cue conditions, regardless of gain or loss outcomes.ConclusionThese findings suggest that Individuals with SVA are more susceptible to the influence of short video-related cues, more sensitive to income loss, and more likely to pursue higher rewards, resulting in higher-risk decisions. The fNIRS results provide critical insights into encouraging healthy short video consumption, informing psychological clinical therapy, and advancing research on addiction-related brain mechanisms.